Assessment of Probiotic Viability during Cheddar Cheese Manufacture and Ripening Using Propidium Monoazide-PCR Quantification - Desfossés-Foucault, Emilie; Dussault-Lepage, Veronique; Le Boucher, Clementine; Savard, Patricia; LaPointe, Gisèle; Roy, Denis (Frontiers in Microbiology, 2012)
The use of a suitable food carrier such as cheese could significantly enhance probiotic viability during storage. The main goal of this study was to assess viability of commercial probiotic strains during Cheddar cheesemaking and ripening (four to six months) by comparing the efficiency of microbiological and molecular approaches. Molecular methods such as quantitative PCR (qPCR) allow bacterial quantification, and DNA-blocking molecules such as propidium monoazide (PMA) select only the living cells’ DNA. Cheese samples were manufactured with a lactococci starter and with one of three probiotic strains (Bifidobacterium animalis subsp. lactis BB-12, Lactobacillus rhamnosus RO011 or Lactobacillus helveticus RO052) or a mixed culture containing B. animalis subsp. lactis BB-12 and L. helveticus RO052 (MC1), both lactobacilli strains (MC2) or all three strains (MC3). DNA extractions were then carried out on PMA-treated and non-treated cell pellets in order to assess PMA treatment efficiency, followed by quantification using the 16S rRNA gene, the elongation factor Tu gene (tuf) or the transaldolase gene (tal). Results with intact/dead ratios of bacteria showed that PMA-treated cheese samples had a significantly lower bacterial count than non-treated DNA samples (P<0.005), confirming that PMA did eliminate dead bacteria from PCR quantification. For both quantification methods, the addition of probiotic strains seemed to accelerate the loss of lactococci viability in comparison to control cheese samples, especially when L. helveticus RO052 was added. Viability of all three probiotic strains was also significantly reduced in mixed culture cheese samples (P<0.0001), B. animalis subsp. lactis BB-12 being the most sensitive to the presence of other strains. However, all probiotic strains did retain their viability (log nine cfu/g of cheese) throughout ripening. This study was successful in monitoring living probiotic species in Cheddar cheese samples through PMA-qPCR.